Evaluation of neopterin, oxidative stress, and immune system in silicosis - Ergün Recai; Ergün Dilek; Özkan Esin; Eryavuz Onmaz Duygu; Körez Muslu K. (Türk Biyokimya Dergisi)
The onset and advancement of silicosis are intricately linked to immune system activation and oxidative stress. We aimed to examine whether occupational silica exposure induces alterations in neopterin levels, the immune system, or the oxidant/antioxidant system.